Jesus the Healer in the Gospels, the Acts of the Apostles, and Early Christianity - Moles, John L. (Histos, 2011)
This paper argues that the Gospels and Acts of the Apostles contain sustained and substantial punning on the name of 'Jesus' as 'healer' and explores the implications for the following: the interpretation and appreciation of these texts, including the question of whether (if at all) they function as Classical texts and the consequences of an affirmative (however qualified): present-day Classicists should be able to 'speak to them', and they in turn should 'respond' to such Classical addresses, to the benefit not only of New Testament scholarship but also of Classicists, who at a stroke acquire five major new texts; the constituent traditions of these texts; the formation, teaching, mission, theology, and political ideology of the early Jesus movement, and its participation in a wider, public, partly textual, and political debate about the claims of Christianity; and the healing element of the historical Jesus’ ministry.